The influence of financial socialisation agents on financial knowledge, financial self-efficacy and financial behaviour among South African consumers - Maswena, Kaelo (Rhodes University, Faculty of Commerce, Department of Management)
There is a need to promote positive financial behaviour in South Africa. According to the Human Sciences Research Council (2018), South African financial behaviour culture emphasises a financially vulnerable nation in terms of not having enough income for future planning and lacking financial self-control. In its key role in influencing financial behaviour, financial socialisation, which is characterised by interactions with indirect, or purposive financial education and communication of financial norms influencing financial behaviours, attitudes, knowledge, capabilities, and self-efficacy of consumers, is the topic of this study. The purpose of the study was to investigate the influence of financial socialisation agents on financial (actual and self-assessed) knowledge, financial self-efficacy and financial behaviour among South African consumers. Based on Glenn's (2018) framework, Xiao et al. (2009) socialisation and Moschis et al. (1978) consumer socialisation theory, the financial socialisation theoretical framework is provided for this study. Literature review provided an overview of past studies on the concepts of financial socialisation, financial (actual and self-assessed) knowledge, financial self-efficacy and financial behaviour. Therefore, a positivistic research paradigm was adopted, which used a cross-sectional correlational research methodology. This study analysed data primarily collected by a questionnaire survey of South African social attitudes to financial literacy by the Human Sciences Research Council (2011), using a multi-staged sampling technique in all South African provinces of consumers of 16 years and older. Descriptive statistics showed that most respondents were black African females between the ages of 26 and 35 years. Most held Matric certificates and were in paid employment for 30 hours or more per week. Most respondents considered family to be the most influential financial socialisation agent, followed by friends, then the bank. Actual financial knowledge of respondents, was indicated as relatively high. Results on self-assessed financial knowledge showed that most of the respondents considered their level of financial knowledge to be neutral. Using Pearson product-moment correlations to measure the strength and correlations of relationships, positive significant correlations were found between financial socialisation agents, financial (actual and self-assessed) knowledge and financial self-efficacy, while a negative and insignificant correlation was found between financial socialisation agents and financial behaviour. Multiple regression analysis results testing the hypotheses of the study demonstrated that financial socialisation agents have a significant positive influence on financial (actual and self-assessed) knowledge and financial self-efficacy; a significant influence on financial behaviour was not reported. Self-assessed financial knowledge showed a positive significant influence on financial self-efficacy and actual financial knowledge had an insignificant negative influence on financial self-efficacy. Actual financial knowledge had a significant positive influence on financial behaviour, whereby a positive yet insignificant relationship was found between self-assessed knowledge and financial behaviour. In the end, recommendations for the results indicate that financial educators need to develop a financial education plan that will include other content areas of financial knowledge such as identified by Huston (2010) and Lusardi and Mitchell (2011); the most important recommendation would be to help consumers have an accurate understanding of their own level of financial knowledge and to improve financial self-efficacy in consumers, financial socialisation experiences such as offering encouragement to open a bank account, to save and invest money, and presenting opportunities to practise financial skills, may increase consumers' self-efficacy and lead to positive financial behaviours.
Keywords: Financial literacy -- South Africa; Finance, Personal -- South Africa; Budgets, Personal -- South Africa; Consumer behavior -- South Africa; Consumers Attitudes; Life skills -- South Africa; Social learning -- South Africa; Self-control -- South Africa; Socialization -- South Africa; Financial socialisation agents